STUDY ON THE POSSIBILITY OF HIGHLIGHTING INVARIANTS OF MOTION IN MARTIALARTS KATA EXERCISES - Viorel Petru, Ardelean; Joseph de Hillerrin, Pierre; Bidiugan, Radu (Arena-Journal of Physical Activities, 2014)
Introduction: Martial arts are practiced both as a hobby, for physical and psychological training, as well as professional sport with its own rules and competitions. How is performed every move in karate is highly important. In this article we analyze some movement in kata exercises. The purpose of this paper is to demonstrate the existence of stable aspects of movement - motion invariant during the execution of technical elements of kata. Our application was made on the kata Heian Nidan. Working methodology consisted in achieving some tests relating to kinematic characteristic of motion, in the kata mentioned before. We use an inertial navigation system that contains 17 sensors - MVNBiomech, produced by Dutch company XSENS Technologies BV. Female athlete tested holds a black belt, she practice karate for 8 years and have 22 years old. The results obtained refers to the oscillation of CGM height, on a total of 12 repetitions from kata sequence selected. The average values of height oscillation to CGM = max. 92 cm and min. 72 cm., St. dev. is Min. = 0.002 and Max.= 0,013 while C.V. = max. 1.7%. Conclusions drawn from the above results indicate that the average values are representative and homogeneity is high. Thus we can say that the invariants (general form of repetitive motion), can be recognized in the development of technical elements of martial arts kata exercises (and we can say in other sports). This emphasis of movement patterns can be useful both referees and coaches involved in the educational process.